Adipic acid formation from cyclohexanediol using platinum and vanadium catalysts: elucidating the role of homogeneous vanadium species. Issue 13 (10th June 2020) - Rogers, Owen; Pattisson, Samuel; Engel, Rebecca V.; Jenkins, Robert L.; Whiston, Keith; Taylor, Stuart H.; Hutchings, Graham J.
Abstract : The applicability of platinum and vanadium catalysts for the production of adipic acid from cyclohexanediol is severely limited by the instability of the latter species in liquid phase reactions. Abstract : Vanadium compounds have shown great potential alongside Pt/C for the oxidation of cyclohexanediol to adipic acid. However, the low stability of these materials often leads to ambiguity when considering the homogeneous or heterogeneous nature of the active species. In this article we describe our attempts to synthesise stable vanadium catalysts through the utilisation of vanadium bronze structures. By the addition of sodium, copper or silver into these structures, leaching could be decreased to 5% for AgVO3, compared to 88.4% with V2 O5 . These reactions were run in aqueous conditions under 3 bar O2 . However, despite significant stabilisation of vanadium in the bronze structures, we show that as little as 7.6 ppm of a homogeneous vanadium species in the reaction solution can cause the selective oxidation of 2-hydroxycyclohexanone to adipic acid. Analysis of the speciation by 51 V NMR and UV-vis has revealed the active species to be in the +5 oxidation state in the form of a decavanadate compound with the presence of small amounts of monovanadate.